2020
DOI: 10.1155/2020/6917185
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Th17 Cells and IL-17 in Th2 Immune Responses of Allergic Conjunctivitis

Abstract: Allergic conjunctivitis (AC) is a common allergic disease that is often associated with the onset of rhinitis or asthma. The incidence of AC has increased significantly in recent years possibly due to air pollution and climate warming. AC seriously affects patients’ quality of life and work efficiency. Th (T-helper) 2 immune responses and type I hypersensitivity reactions are generally considered the basis of occurrence of AC. It has been found that new subpopulations of T-helper cells, Th17 cells that produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 120 publications
(160 reference statements)
2
9
0
Order By: Relevance
“…6 The role of IL-17A in allergic and atopic diseases is unclear. The current findings shown in Table 1 are in accordance with those of a previous study, which showed that activation of Th17 cells promoted Th2 activity and was associated with symptoms of allergy, 20,21 such as allergic conjunctivitis and allergic rhinitis. This could be explained by the common pathophysiology of all atopic diseases such as asthma and allergic conjunctivitis.…”
Section: Discussionsupporting
confidence: 92%
“…6 The role of IL-17A in allergic and atopic diseases is unclear. The current findings shown in Table 1 are in accordance with those of a previous study, which showed that activation of Th17 cells promoted Th2 activity and was associated with symptoms of allergy, 20,21 such as allergic conjunctivitis and allergic rhinitis. This could be explained by the common pathophysiology of all atopic diseases such as asthma and allergic conjunctivitis.…”
Section: Discussionsupporting
confidence: 92%
“…22 IL-6 is recognized as a marker of allergic asthma, 23 and is also the major regulator in the differentiation and function of Th17 cells, 24 which play an important role in the Th2-mediated allergic response through the production of IL-17. 25 The elevated levels of supernatant IL-33 and IL-6 from AR-NFs indicates an extensive immune-regulatory and also important proinflammatory roles of NFs in the development of AR. Inhibition the expression of these cytokines released from NFs is helpful to alleviate the progression of AR.…”
Section: Discussionmentioning
confidence: 99%
“…These allergies and B cells produce IgE, mast cell growth, and aggregation of eosinophil cells 16 . Eosinophil cells release histamine expression and induce conjunctival allergic reaction, such as hyperemia, microvascular permeability, cytokine secretion, etc 17 . It has been reported that PM 2.5 triggers AC by inducing serum IgE.…”
Section: Discussionmentioning
confidence: 99%